Making and agreeing to requests in Old Tibetan - Hill, Nathan (My University, 2023)
The verbs གསོལ་ gsol ‘request’ and གནང་ gnaṅ ‘agree, grant', because of their complementary semantics and parallel syntax, provide a convenient window through which to caste light on the two forms of subordinate clauses that they both govern, namely infinitives and terminative verbal nouns.
PUBLISHED
Keywords: Old Tibetan; Switch reference; Subordination